Chiral Inductive Diastereoconvergent Allylation Reactions of Allyltrimethylsilane and Diastereomixtures of Diarylmethanols Catalyzed by FeCl3. Issue 46 (30th October 2018) - Fujihara, Rina; Nakata, Kenya
Abstract : We report the chiral‐auxiliary‐controlled diastereoconvergent allylation reactions of allyltrimethylsilane with diastereomeric mixtures of diarylmethanols in the presence of FeCl3 as a Lewis acid catalyst. This reaction was successfully applied to a variety of substrates; it proceeded irrespective of the substituent on the aromatic ring of the substrate. The present method was used as the key step in synthesizing ( R )‐tolterodine. Abstract : Diastereoconvergent Manner: FeCl3 ‐catalyzed chiral‐auxiliary‐controlled diastereoconvergent allylation reactions of allyltrimethylsilane with diastereomeric mixtures of diarylmethanols were achieved with high yields and selectivities.